Leadership role in promoting childhood education: Perception of practitioners in Pakistan - Syed Jawad Zareen Shah; Muhammad Imran Yousuf; Muhammad Imran; Muhammad Hanif (Institute of Advanced Engineering and Science, 2023)
Early childhood care and education (ECCE) is a significant stage to develop responsible generations. Holistic child development may be possible through a plan of early childhood education (ECE) and early learning. This study is planned to explore the role of school leadership in promoting ECCE in Azad Jammu & Kashmir (AJK), Pakistan. This research study may play a significant role in sensitizing the educationist, practitioners, pedagogical leadership in early learning centers, and political leadership. The study was quantitative in nature. In the first step, a stratified sampling technique was used to select the districts among the three divisions of AJK. In the second step, a simple random sampling technique was used. Self-developed a five-point Likert scale questionnaire was used to collect the data. The study concluded that leadership plays a significant role in promoting ECCE. It is encouraging that educational leadership involves parents in the process of teaching-learning. Learners are happy in the school activities, and academic leadership is planning to minimize the workload of kids. It is recommended that children may be facilitated with better infrastructure.